OPTICAL SOLITONS TO THE FRACTIONAL PERTURBED NLSE IN NANO-FIBERS - Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Baskonus, Haci Mehmet (Amer Inst Mathematical Sciences-Aims, 2020)
In this paper, we study the space-time fractional perturbed nonlinear Schrodinger equation under the Kerr law non-linearity by using the extended sinh-Gordon equation expansion method. The perturbed nonlinear Schrodinger equation is a nonlinear model which arises in nano-fibers. Some family of optical solitons and singular periodic wave solutions are successfully revealed. The parametric conditions for the existence of valid solitons are stated. Under the choice of suitable values of the parameters, the 3-dimensional and 2-dimensional graphs to some of the reported solutions are plotted.
Keywords: Sinh-Gordon equation; perturbed NLSE; nano-fibers; fractional order; optical solitons